Synthesis And Characterization Of 3d Transition Metal Complexes With Schiff Base Ligands - Tan, Sze Yee (Universiti Malaysia Sarawak (UNIMAS), 2011)
There are two kinds of Schiff base ligands have been synthesized and characterized in this research project work. The first ligand was derived by the condensation reaction of benzoylacetone and ethylenediamine, whereas the second ligand was derived by the condensation of benzyhydrazide and 2-hydroxy-l-naphthaldehyde. Both Schiff base ligands have been reacted with metal(II) ions such as Fe(II), Ni(II), Cu(II), Co(II) and Zn(H) ions, respectively. Two Schiff base ligands and their metal complexes have also been characterized by UV-visible, FTIR and lH NMR spectroscopic techniques. The first ligand was acted as dinegative tetradentate nature while the second ligand was acted as dinegative tridentate nature towards metal(II) ions, respectively. All the metal complexes have coordination number of four (4). All metal complexes are non electrolyte in nature.